Mixture Compound Fertilizer and Super Absorbent Polymer Application Significantly Promoted Growth and Increased Nutrient Levels in Pinus massoniana Seedlings and Soil in Seriously Eroded Degradation Region of Southern China - Mao, Lanhua; Zha, Ruibo; Chen, Shifa; Zhang, Jing; Jie, Ling; Zha, Xuan (Frontiers in Plant Science, 2021)
Pinus massoniana is the pioneer tree species in the red soil regions of southern China, however, the serious understory soil erosion and nutrient deficiency in that region are the main factors restricting the growth of P. massoniana. This field study examined the effects of compound fertilizer and super absorbent polymer (SAP) on the physiology, growth characteristics, biomass, soil nutrient, plant nutrient content, and nutrient uptake efficiency of 1-year-old P. massoniana seedlings for 2 years at Changting, Fujian in South China. One control (no fertilizer, CK) and fertilization treatments were established, namely, single compound fertilizer application (0.94, 1.89, and 3.56 g⋅plant–1) and mixture compound fertilizer and SAP application (0.94 + 1.01, 1.89 + 1.01, and 3.56 + 1.01 g⋅plant–1). Fertilization significantly improved the physiological performance, root collar diameter growth, height growth, biomass, and nutrient uptake of the seedlings. Compared with other fertilization treatments, the mixture compound fertilizer and SAP application significantly improved the seedling photosynthesis, which meant that the SAP had a significant effect on promoting photosynthesis. Under the mixture compound fertilizer and SAP application, the whole biomass of the seedlings was higher than that of all other treatments. Fertilization significantly increased the nitrogen (N), phosphorus (P), and potassium (K) content in the soils, leaves, stems, and roots of the seedlings, respectively. The P content was the main factor affecting growth characteristics and contributed to 58.03% of the total variation in seedling growth characteristics (P < 0.01). The N:P ratio of CK in the soils, leaves, and stems were higher than that of all the fertilization treatments, indicating that the severely eroded and degraded region had little P and required much of P. The principal component analysis indicated that the F2S (1.89 + 1.01 g) was the optimum fertilization amount and method in this experiment. These results provide a theoretical basis for the fertilization management of P. massoniana forests with severely eroded and degraded red soil regions.